A Comparison of Allograft Survival Between Cyclosporine and Tacrolimus Based Immunosuppressive Therapy in Kidney Transplantation: BIRDEM General Hospital Experience - Mitra, Palash; Rahman, Md Anisur; Rahim, Muhammad Abdur; Ananna, Mehruba Alam; Samdani, Tasrina Shamnaz; Sumon, Ahmed Sharif; Akhtar, Moontasim; Kabir, Md Hasanul; Haque, Mirza Shariful; Pappu, Md Hedayetul Islam; Billah, Md Mostarshid; Chowdhury, Tufayel Ahmed; et al. (BIRDEM Medical Journal, 2016)
Introduction and Aims: Calcineurin inhibitors (CNIs), cyclosporine and tacrolimus, are one of the three major components of basic immunosuppressive therapy of kidney transplantation. Our aims were to study and compare the early and long-term graft survival in kidney transplant recipients who were receiving either of these two CNIs. Methods: A questionnaire was formed and data were collected from the hospital records. We divided the patients in group 1 (patients on cyclosporine) and group 2 (patients on tacrolimus). We retrospectively evaluated patients clinical and laboratory findings. Results: Group 1 included 50 patients who were on cyclosporine and group 2 included 61 patients who were on tacrolimus. Patients receiving tacrolimus showed almost similar renal function as cyclosporine receiving patients; serum creatinine was 1.27 ± 0.56 versus 1.42 ± 0.91mg/dL (p = 0.258), but they required less time for serum creatinine to become normal (4.71 ± 2.3 versus 7.26 ± 5.6 days, p=0.001) and less duration of post-transplant hospital stay (11.38 ± 3.33 versus 13.65 ± 5.0 days, p = 0.005). New onset diabetes was more pronounced in group 2 (29.5% versus 12 %, p = 0.025). On the other hand, acute rejection was only noted in group 1 (2 versus 0, p = 0.014). One-year and three-year graft survival for cyclosporine was 92.0% and 83.3%, and for tacrolimus was 96.2% and 89.2% respectively. Conclusions: Tacrolimus is relatively favourable to cyclosporine in preventing acute allograft rejection and better immediate post-transplant graft function recovery. Birdem Med J 2015; 5(2): 78-81